Dissecting intratumoral myeloid cell plasticity by single cell RNA‐seq. (29th April 2019) - Song, Qianqian; Hawkins, Gregory A.; Wudel, Leonard; Chou, Ping‐Chieh; Forbes, Elizabeth; Pullikuth, Ashok K.; Liu, Liang; Jin, Guangxu; Craddock, Lou; Topaloglu, Umit; Kucera, Gregory; O'Neill, Stacey; et al.
Abstract: Tumor‐infiltrating myeloid cells are the most abundant leukocyte population within tumors. Molecular cues from the tumor microenvironment promote the differentiation of immature myeloid cells toward an immunosuppressive phenotype. However, the in situ dynamics of the transcriptional reprogramming underlying this process are poorly understood. Therefore, we applied single cell RNA‐seq (scRNA‐seq) to computationally investigate the cellular composition and transcriptional dynamics of tumor and adjacent normal tissues from 4 early‐stage non‐small cell lung cancer (NSCLC) patients. Our scRNA‐seq analyses identified 11 485 cells that varied in identity and gene expression traits between normal and tumor tissues. Among these, myeloid cell populations exhibited the most diverse changes between tumor and normal tissues, consistent with tumor‐mediated reprogramming. Through trajectory analysis, we identified a differentiation path from CD14+ monocytes to M2 macrophages (monocyte‐to‐M2). This differentiation path was reproducible across patients, accompanied by increased expression of genes (eg, MRC1 / CD206, MSR1 / CD204, PPARG, TREM2 ) with significantly enriched functions (Oxidative phosphorylation and P53 pathway) and decreased expression of genes (eg, CXCL2, IL1B ) with significantly enriched functions ( TNF‐α signaling via NF‐κB and inflammatory response). Our analysis further identified a co‐regulatory network implicating upstream transcription factors ( JUN, NFKBIA ) in monocyte‐to‐M2 differentiation, and activated ligand‐receptor interactions (eg, SFTPA1 ‐ TLR2, ICAM1 ‐ ITGAM ) suggesting intratumoral mechanisms whereby epithelial cells stimulate monocyte‐to‐M2 differentiation. Overall, our study identified the prevalent monocyte‐to‐M2 differentiation in NSCLC, accompanied by an intricate transcriptional reprogramming mediated by specific transcriptional activators and intercellular crosstalk involving ligand‐receptor interactions. Abstract : Single‐cell RNAseq reveals the transcriptional path from monocyte to M2 macrophage. M2 differentiation in NSCLC is driven by a multifaceted co‐regulatory network. Epithelial‐immune cell ligand‐receptor interactions associate with M2 differentiation